Pendampingan Mahasiswa Program Studi Administrasi Publik FISIP Uncen dalam Membangun Jiwa Kepemimpinan yang Berintegritas : Mentoring Students of the Public Administration Study Program, FISIP Uncen in Building a Spirit of Leadership with Integrity - Sapioper, Hiskia C. M.; Gainau , Aldrin Watson; Fatem , Agustinus (Assoeltan: Indonesian Journal of Community Research and Engagement, 2025)
One of the qualities and characteristics required in leadership is integrity. The main issue raised was the lack of awareness and consistency among students in demonstrating leadership behavior based on integrity values. This service aims to shape and strengthen integrity-based leadership among students in the Public Administration Study Program, Faculty of Social and Political Sciences, Cenderawasih University, by viewing students as agents of change and aspiring leaders. The method used was Participatory Action Research (PAR), which included interactive lectures, discussions (FGDs), and question-and-answer sessions delivered to fourth and sixth semester students. Evaluations were conducted before and after the activity to measure the increase in students' knowledge and understanding of integrity-based leadership. The results of this community service activity showed high student enthusiasm for the material, as well as an increase in conceptual understanding of the importance of values- and character-based leadership. The discussion also revealed that the lack of participation in student organizations was due to a lack of guidance and supporting facilities. Supporting factors for this activity included students' awareness of the importance of their role as aspiring leaders and the availability of curriculum support. Conversely, inhibiting factors included low participation in organizations and limited extracurricular activities. This activity emphasized that leadership is not an innate trait, but rather a skill that must be developed through learning and internalization of values. Recommendations provided include the need for further training and institutional support in the form of funding and facilities for student organizations.